Recurrent atrial fibrillation with fast ventricular rate in an elderly lady: old records reveal cause of the malady - Bhende, Punam; Mannari, Jyoti; Wagh, Rishikesh; Parikh, Vrajesh; Talavia, Rahul; Patel, Naman; Chaudhary, Ramesh; Patel, Mansi; Rathod, Mehul (International Journal of Research in Medical Sciences, 2025)
Amiodarone is an iodinated benzofuran derivative and is prescribed widely in management of arrythmias- ventricular and supraventricular alike. Excellent efficacy, minimal negative inotropic activity and less rate of ventricular pro arrhythmia makes it the choice of drug in heart failure. Side effects however, make it a drug to be used with caution and they range from pulmonary toxicity to thyroid dysfunction. 15-20% of patients treated with amiodarone are believed to develop some thyroid dysfunction. It can cause amiodarone induced hypothyroidism (AIH) or amiodarone induced thyrotoxicosis (AIT). AIT usually is seen in areas with low uptake of iodine and AIH in areas with sufficient iodine uptake. We report a case of 58-year-old lady with rheumatic heart disease who was started on amiodarone for atrial fibrillation and later presented with recurrent atrial fibrillation (AF) with fast ventricular rate (FVR) and diagnosed as AIT. The challenges in diagnosis and management are discussed.